2007
DOI: 10.1016/j.neuropsychologia.2007.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between cerebellar asymmetry and handedness in chimpanzees (Pan troglodytes) and capuchins (Cebus apella)

Abstract: A comparative study of chimpanzee (Pan troglodytes) and capuchin monkey (Cebus apella) cerebellar asymmetry and its relationship to handedness was conducted. Magnetic resonance images of the brain and behavioral data on a coordinated bimanual task were obtained from 16 chimpanzees and 11 capuchins. Chimpanzees displayed a greater rightward bias of the posterior cerebellum and capuchins displayed a greater leftward bias of the anterior cerebellum. Cerebellar asymmetries were significantly associated with handed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
28
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 46 publications
5
28
1
Order By: Relevance
“…In the cerebellum, anteriorly left-biased and posterior right-biased absolute volumes of the cerebellum were reported as an intrinsic cerebellar asymmetry [13,34], indicating a clockwise cerebellar torque. A similar clockwise torque pattern was seen in the cerebellum of chimpanzees [14]. In contrast, a counterclockwise cerebellar torque (rostrally leftward biased, and caudally rightward biased or symmetrical) was revealed in the cerebellum of ferrets [15].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…In the cerebellum, anteriorly left-biased and posterior right-biased absolute volumes of the cerebellum were reported as an intrinsic cerebellar asymmetry [13,34], indicating a clockwise cerebellar torque. A similar clockwise torque pattern was seen in the cerebellum of chimpanzees [14]. In contrast, a counterclockwise cerebellar torque (rostrally leftward biased, and caudally rightward biased or symmetrical) was revealed in the cerebellum of ferrets [15].…”
Section: Discussionsupporting
confidence: 62%
“…The direction and extent of the cerebellar torque asymmetry varied depending on species [13,14,34], the hand preference [13], and/or sex [34], independent of genetic factors [13]. The extent of torque asymmetry and the volume laterality of the cerebellum were more enhanced in males than in females in ferrets [15], as well as humans [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One aim of this study was to examine whether chimpanzees show any evidence of a torque asymmetry in the cerebellum, such as that described by Snyder et al (1995). A preliminary comparative study between 16 capuchin monkeys and chimpanzees showed that apes had a rightward asymmetry in the anterior but not posterior region of the cerebellum (Phillips & Hopkins, 2007), and the goal of the present study was to more fully explore the potential influence of sex, rearing history, and age on cerebellar volume and lateralization.The second aim of this study was to assess the potential association between handedness and lateralization in the cerebellum. Phillips and Hopkins (2007) failed to find an association between handedness for coordinated bimanual actions and cerebellar asymmetries in their smaller sample of chimpanzees, although the association was significant in the capuchin monkeys.…”
mentioning
confidence: 91%
“…A preliminary comparative study between 16 capuchin monkeys and chimpanzees showed that apes had a rightward asymmetry in the anterior but not posterior region of the cerebellum (Phillips & Hopkins, 2007), and the goal of the present study was to more fully explore the potential influence of sex, rearing history, and age on cerebellar volume and lateralization.…”
mentioning
confidence: 97%